ANALISIS KETERAMPILAN PROSES SAINS DAN MINAT BELAJAR SISWA PADA PEMBELAJARAN DARING MENGGUNAKAN MEDIA MICROSOFT TEAMS - Novita Nurul Firdaus; Hasan Subekti (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
This research was conducted to analyze science process skills (SPS) and students' interest in learning at SMP Negeri 62 Surabaya while learning uses media Microsoft Teams. This type of research is categorized as descriptive quantitative. The participants selected in this study were students of class VIII B, with 35 students. The instrument used in this study was a test instrument with 18 multiple choice questions covering 6 SPS indicators and a non-test instrument in the form of a questionnaire containing 20 selected questions. This research using descriptive data analysis techniques. The research’s results are obtaining an average SPS level for class VIII B students in the sufficient group with a percentage of 52%. The highest skill is in the conclusion indicator with percentage of 74%, while the students’ lowest skill is in the indicator measuring with a large percentage of 20%. For the average student interest in learning using media, it falls into the very interested group with a total percentage of 74.2%. It can be concluding that the level of SPS for grade VIII B students of SMP Negeri 62 Surabaya is in the sufficient group so that there is a need for improvement in the SPS-based learning process and students' interest in online learning is in the very interested group so that media is Microsoft Teams suitable for use in the learning process. The implication of this research can be used as a reference and separate in designing learning that can increase SPS and student interest in learning.